Associations between dietary magnesium intake and handgrip strength were modified by serum vitamin D level among the US elderly - Han, Shuang; Gao, Yue; Gan, Da (Frontiers in Nutrition, 2022)
Objective: The present study aimed to evaluate the associations between dietary magnesium intake and handgrip strength, and whether these associations were affected by serum vitamin D status. Methods: A total of 2127 participants aged 60 and above from the National Health and Nutrition Examination Survey (NHANES) of the 2011-2014 cycles were included in the analyses. Magnesium intake was obtained by 24-hour dietary recalls and 30-day dietary supplement. Participants in the lowest sex-specific tertile of magnesium intake were defined as having low magnesium intake. Serum 25-hydroxyvitamin D [25(OH)D)] concentrations were examined by using ultra-high performance liquid chromatography tandem mass spectrometry and categorized into three levels: deficient, suboptimal, and sufficient. Handgrip strength was determined by using a dynamometer. Multivariable linear regression models were used to investigate the associations between dietary magnesium intake and handgrip strength. Results: Low magnesium intake was not associated with handgrip strength, but interactions between low magnesium intake and serum 25(OH)D level existed on handgrip strength. The stratified analyses found that only in participants with deficient serum 25(OH)D, low magnesium intake was associated with reduced handgrip strength. The combined analyses shown that participants with both low magnesium intake and deficient serum 25(OH)D had highest decrease of handgrip strength. Conclusion: Findings suggested that low magnesium intake was associated with reduced handgrip strength only in participants with deficient serum 25(OH)D. Increased magnesium intake was recommended for participants with deficient serum 25(OH)D in maintaining muscle strength.